Synthesis and Characterization of Molecularly Imprinted Polymer for the Removal of Triazine Herbicides in Water Samples - Rachel Marcella, Roland (UNIMAS Institutional Repository, 2024)
Cyanazine (CYZ), Ametryn (AME) and Atrazine (ATZ) are mostly utilized 1, 3, 5-triazine herbicides to control the growth of broadleaf grasses and weeds, however, their extensive usage has adverse effects on the environment, non-target organisms, and human health. Therefore, molecularly imprinted polymers (MIPs) were applied to remove triazine herbicides in the environment. In this study, MIPs of triazine herbicides were synthesized by precipitation polymerization in the presence of template molecules (CYZ, AME and ATZ), functional monomers (methacrylic acid, acrylamide, 2-vinylpyirdine, and 4-vinylpyridine), cross-linker (ethylene glycol dimethacrylate), initiator (azo-bis-isobutyronitrile), and solvent (toluene and acetonitrile). For comparison study, the non-imprinted polymers (NIPs) were synthesized without the addition of template molecule. The Fourier Transform Infra-Red (FTIR) analysis of MIPs of triazine herbicides indicated the presence of CYZ, AME and ATZ were observed at ~756 cm–1, ~1450 cm–1, and ~1389 cm–1, respectively. MIP (AAm) of CYZ had its maximum adsorption efficiency in 6 ppm CYZ solution at pH 7, 0.1 g of polymer and 240 mins of contact time. MIP (MAA) of AME had its highest adsorption efficiency in 7 ppm AME solution at pH 7, 0.1 g of polymer and 210 mins of contact time. MIP (2VP) of ATZ exhibited its maximum adsorption efficiency in 8 ppm of ATZ solution at pH 7, 0.3 g of polymer and 15 mins of contact time. The thermogravimetric analysis (TGA) of MIPs of triazine herbicides depicted that the decomposition of polymers was between ~320 °C to ~500 °C. MIP (AAm) of CYZ, MIP (MAA) of AME and MIP (2VP) of ATZ were more selective towards their target compounds with relative selectivity coefficients of 2.36, 2.66 and 2.77, respectively. The synthesized MIP (AAm) of CYZ, MIP (MAA) of AME and MIP (2VP) of ATZ were successfully applied to remove CYZ, AME and ATZ from different water samples (distilled water, tap water and river water) with removal efficiencies between ~84% to ~95%.